Preclinical Study of Single-Dose Moxidectin, a New Oral Treatment for Scabies: Efficacy, Safety, and Pharmacokinetics Compared to Two-Dose Ivermectin in a Porcine Model - Bernigaud, Charlotte; Fang, Fang; Fischer, Katja; Lespine, Anne; Aho, Ludwig Serge; Dreau, Dominique; Kelly, Andrew; Sutra, Jean-François; Moreau, Francis; Lilin, Thomas; Botterel, Françoise; Guillot, Jacques; et al. (PLOS Neglected Tropical Diseases, 2016)
Author Summary Scabies caused by the Sarcoptes scabiei mite affects many people worldwide and has been recently recognized by the WHO as a truly neglected tropical disease. Currently available treatments are insufficient to overcome this insidious disease and its co-morbidities for example impetigo, rheumatic heart disease and post-streptococcal glomerulonephritis. Treatment management is a major issue, as problems with compliance as well as mite resistance to current drugs are reported. Data have accumulated indicating that moxidectin could be a genuine new candidate drug for sustainable scabies control. To provide proof of concept, we utilized an experimental scabies pig model that closely resembles the human route of scabies infection. We demonstrated that a single moxidectin dose, when compared with the currently recommended two-doses ivermectin treatment routine, achieved a better and faster acaricidal efficacy. Importantly, the skin half-life of moxidectin is longer, potentially covering the entire mite life cycle. Our baseline data demonstrate in principle the potential and feasibility of moxidectin treatment for scabies, thereby enabling the move into larger high-powered efficacy and dose ranging studies in human populations. Moxidectin could indeed play a game-changing role in scabies control and has the potential to accelerate the steps towards elimination of this insidious disease.